The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.2006.0030-1299.15331.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of within‐patch characteristics on the vulnerability of a plant to herbivory

Abstract: Consumption of a focal plant by herbivores depends, not only on the physical and chemical characteristics of that plant, but also on the characteristics of the neighbouring vegetation. Consumption of focal plants has been related to their own characteristics and to the quality of the neighbouring vegetation, but the two have not been combined to examine the relative importance of focal plant and neighbouring vegetation characteristics. We conducted a series of feeding trials to examine the relative importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 59 publications
3
46
1
1
Order By: Relevance
“…High densities of rabbits are able to completely prevent regeneration of woody species in abandoned fields (Oosterveld, 1983). Small herbivores like red-bellied pademelons (Thylogale billardierii) even select seedlings to consume in an unpalatable neighbourhood (Miller et al, 2007). At our study sites, rabbits were present in low densities, but burrows were concentrated in bramble thickets.…”
Section: Bramble and Tall Herb Patches As Safe Sitesmentioning
confidence: 82%
“…High densities of rabbits are able to completely prevent regeneration of woody species in abandoned fields (Oosterveld, 1983). Small herbivores like red-bellied pademelons (Thylogale billardierii) even select seedlings to consume in an unpalatable neighbourhood (Miller et al, 2007). At our study sites, rabbits were present in low densities, but burrows were concentrated in bramble thickets.…”
Section: Bramble and Tall Herb Patches As Safe Sitesmentioning
confidence: 82%
“…The difference in plant species diversity is a typically important characteristic of heterogeneity, and diverse plant communities can markedly affect foraging strategies of large herbivores and their concomitant impacts on the dynamics of vegetation itself (Bergvall et al, 2006;Miller et al, 2007;Wang et al, 2011). Our previous work found that complex spatial neighborhood of several plant species makes the palatable species for herbivores to less selected, contributing to the maintenance of plant diversity (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, how the patterns of spatial association between plants defend against herbivory has not been empirically explored. Recently, an increasing number of empirical studies have focused on how the spatial neighboring relationship between preferred and non-preferred species affects herbivory risk (Miller et al 2007;Bergvall et al 2008;Bee et al 2009). Almost all research has been conducted on the basis of two hypotheses.…”
Section: Introductionmentioning
confidence: 99%